Cross-linking of polymer and ionic liquid as high-performance gel electrolyte for flexible solid-state supercapacitors. (1st August 2017) - Zhong, Xiongwei; Tang, Jun; Cao, Lujie; Kong, Weiguang; Sun, Zheng; Cheng, Hua; Lu, Zhouguang; Pan, Hui; Xu, Baomin
Highlights: A facile method to prepare gel polymer electrolyte with high conductivity is proposed. A flexible symmetric capacitor based on the prepared GPE shows ultra-flexibility. The capacitor with high voltage can power up a 3.0 V LED even bended to a angle of 180°. Abstract: It is highly desirable to develop flexible solid-state electrochemical double-layer capacitors (EDLCs) with non-liquid electrolyte. However, it is still a great challenge to prepare gel polymer electrolyte (GPE) possessing high ionic conductivity and good mechanical property. In this work, a simple and novel method to improve the conductivity and mechanical properties of GPE film for their applications as electrolyte and separator in EDLC is presented. The GPE film is prepared by cross-linking ionic liquid (IL) with poly (ethylene oxide) (PEO) and benzophenone (Bp) followed by ultraviolet (UV) irradiation. Then, a non-woven cellulose separator (FPC) is used to absorb the GPE. By tuning the mass ratio (n) between IL and PEO, the flexible EDLC cooperated with low-cost active carbon and the electrolyte film with n = 10 has a high capacitance of 70.84 F∙g −1, a wide and stable electrochemical window of 3.5 V, an energy density of 30.13 Wh∙kg −1 and a power density of 874.8 W∙kg −1 at a current density of 1 A∙g −1, which can drive a 3.0 V light-emitting diode (LED). Importantly, the excellent performance of the flexible and low-cost EDLC can be maintained at a bending angle up to 180°, indicating the ultra-flexibility. It is expected that the IL-PEO-FPC electrolyte film is a promising candidate of GPE for flexible devices and energy storage systems.